2008
DOI: 10.1007/s10643-008-0234-7
|View full text |Cite
|
Sign up to set email alerts
|

Math Fluency: Accuracy Versus Speed in Preoperational and Concrete Operational First and Second Grade Children

Abstract: Cognitive abilities as well as math fluency play an important role in mathematical skills. Understanding the relationship between cognitive abilities and mathematical skills is imperative to teaching effective arithmetic skills. The present study aimed to investigate the relationship between cognitive ability and math fluency with 38 first and second grade elementary aged children. Results demonstrate that preoperational children lacked the speed of concrete operational children but achieved comparable levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 23 publications
0
15
0
1
Order By: Relevance
“…In order to gain a better understanding of the absolute level of conservation ability, children were classified as conservers (at least five of six correct answers) and nonconservers (fewer than five correct answers) according to the procedure described by Ramos-Christian et al (2008). Conservers were considered to have a reliable understanding of conservation principles.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to gain a better understanding of the absolute level of conservation ability, children were classified as conservers (at least five of six correct answers) and nonconservers (fewer than five correct answers) according to the procedure described by Ramos-Christian et al (2008). Conservers were considered to have a reliable understanding of conservation principles.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have revealed associations between math skills and various conservation abilities even above IQ (e.g., Campbell & Ramey, 1990; Freyberg, 1966; Shayer, Ginsburg, & Coe, 2007) in elementary school children. Studies indicate that nonconserving children in kindergarten and in the early school years differ significantly from conserving children (Conservation of Substance and Number) in math fluency in single-digit arithmetic (addition, subtraction, multiplication, and division) with respect to their accuracy and speed in solving basic rote calculations (e.g., 2 + 3 = 5; 4 × 5 = 20; 45 / 5 = 9) (Cooper & Schleser, 2006; Ramos-Christian, Schleser, & Varn, 2008). Low conservation abilities contribute to difficulties with measurement (Burgard & Roos, 1991) or open-equation problems (e.g., 4 + __ = 12; Steffe, Spikes, & Hirstein, 1976).…”
Section: Mathematical Ability and Conservation Skillsmentioning
confidence: 99%
“…Finally, we wanted to have an index of arithmetic competence, which is a crucial component in math ability. We thus evaluated arithmetic fluency (i.e., the ability to quickly solve arithmetic operations), which is highly critical for efficient arithmetic performance (see for instance, Ramos-Christian, Schleser, & Varn, 2008). To do so, we created a paper-and-pencil test, adapted from the Tempo-Test Rekenen (De Vos, 1992; as in Nys & Content, 2012;Sasanguie et al, 2013).…”
Section: Symbolic Magnitude Comparisonmentioning
confidence: 99%
“…Nonetheless, concrete-operational thinking represents an important prerequisite of formal thinking (Inhelder and Piaget, 1958;Powell and Kalina, 2009). It is associated with a range of learning outcomes and academic achievement (Jordan and Brownlee, 1981;Hattie, 2009), such as maths fluency and maths achievement (conservation ability; Arlin, 1981;Cooper and Schleser, 2006;Ramos-Christian et al, 2008;Krajewski and Schneider, 2009;Wubbena, 2013;Lambert and Spinath, 2018), as well as reading comprehension and reading achievement (conservation and classification ability; Arlin, 1981;Cartwright, 2002;Colé et al, 2014;Cartwright et al, 2017). At the same time, differences in the ability of concrete-operational thinking become clear, as e.g., students with learning disabilities show lower levels of concrete-operational thinking than their peers (Wember, 1986;Riley, 1989;Fakouri, 1991).…”
Section: Concrete-operational Thinkingmentioning
confidence: 99%